2019
DOI: 10.1088/1475-7516/2019/10/031
|View full text |Cite
|
Sign up to set email alerts
|

From primordial black holes abundance to primordial curvature power spectrum (and back)

Abstract: In the model where Primordial Black Holes (PBHs) form from large primordial curvature (C) perturbations, i.e., CPBHs, constraints on PBH abundance provide in principle constraints on the primordial curvature power spectrum. This connection however depends necessarily on the details of PBH formation mechanism. In this paper we provide, for the first time, constraints on the primordial curvature power spectrum from the latest limits on PBH abundance, taking into account all the steps from gravitational collapse … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
107
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 231 publications
(403 reference statements)
2
107
0
1
Order By: Relevance
“…Full consideration of this will require consideration of the the shape of the small-scale power spectrum, typical profile shapes and the shape of the bispectrum, amongst other factors, and goes beyond the scope of this paper. However, much work has been completed on this topic in the past [15,[19][20][21][22][23][24][25]27], and a more complete analysis using the methods presented in this paper would yield qualitatively similar results. We have also only considered an expansion to second order in local-type non-Gaussianity, although it has been shown that higher-order terms can also be important [21].…”
Section: The Primordial Black Hole Merger Ratementioning
confidence: 78%
“…Full consideration of this will require consideration of the the shape of the small-scale power spectrum, typical profile shapes and the shape of the bispectrum, amongst other factors, and goes beyond the scope of this paper. However, much work has been completed on this topic in the past [15,[19][20][21][22][23][24][25]27], and a more complete analysis using the methods presented in this paper would yield qualitatively similar results. We have also only considered an expansion to second order in local-type non-Gaussianity, although it has been shown that higher-order terms can also be important [21].…”
Section: The Primordial Black Hole Merger Ratementioning
confidence: 78%
“…For a given amplitude of the scalar power spectrum, the probability of forming PBHs depends on the statistical properties of the scalar fluctuations, since typically PBH formation is a rare event occurring in the tail of the distribution function. For a gaussian distribution any power spectrum generating stable black holes with ζ 2 10 −2 leads to an overclosure of the universe [48]. For a positive χ 2 -distribution, as expected for the sourced scalar perturbations in axion inflation, this value is lowered to ζ 2 10 −3 [14].…”
Section: Primordial Black Hole Formation and Phenomenologymentioning
confidence: 88%
“…However this scale dependence is smaller than the uncertainties discussed in section 2.1, and therefore we do not include it here 12. To translate from k to M H we use equation(8), from reference[52], which agrees with the conversion given in reference[26]. However we note a discrepancy with reference[59].…”
mentioning
confidence: 91%